The Horde : How the Mongols Changed the World - Favereau, Marie (Cambridge, Massachusetts The Belknap Press of Harvard University Press, 2021)
"The Mongols are universally known as conquerors, but they were more than that: influential thinkers, politicians, engineers, and merchants. Challenging the view that nomads are peripheral to history, The Horde reveals the complex empire the Mongols built and traces its enduring imprint on politics and society in Europe, Asia, and the Middle East"--
Include Illustrations, Maps and Index
Keywords: Civilization. -- History. -- Europe--Golden Horde -- Mongols